Asymmetric synthesis of cytotoxic sponge metabolites R-strongylodiols A and B and an analogue - Kirkham, J; Courtney, T; Lee, V; Baldwin, J (2005)
The asymmetric synthesis of the marine sponge natural products R-strongylodiols A R-1 and B R-2, using a minimum protection strategy, is described. Two approaches were examined and the Noyori asymmetric reduction of ynones was found to be successful for installing the chirality of the natural products. Analogue R-32 was also prepared. In addition, asymmetric alkynylation of aldehydes is briefly reviewed. © 2005 Elsevier Ltd. All rights reserved.